Дослідження методів проектування 3D простору для "triple-a" проектів - Бронов, І. В. (ХНУРЕ, 2024)
The object of research is the methods and means of 3D space design for "triple-A" projects. The purpose of the work is to research the subject area of 3D space design methods for "triple-A" projects, research of existing game drivers, analysis, their comparative analysis and derivation of recommendations. As a result, the optimal modern game engine for the development of AAA projects will be found.
Keywords: 3D-моделювання; triple-A